A mechanosensitive caveolae–invadosome interplay drives matrix remodelling for cancer cell invasion - Monteiro, Pedro; Remy, David; Lemerle, Eline; Routet, Fiona; Macé, Anne Sophie; Guedj, Chloé; Ladoux, Benoit; Vassilopoulos, Stéphane; Lamaze, Christophe; Chavrier, Philippe (Nature Cell Biology, 2023)
Invadosomes and caveolae are mechanosensitive structures that are implicated in metastasis. Here, we describe a unique juxtaposition of caveola clusters and matrix degradative invadosomes at contact sites between the plasma membrane of cancer cells and constricting fibrils both in 2D and 3D type I collagen matrix environments. Preferential association between caveolae and straight segments of the fibrils, and between invadosomes and bent segments of the fibrils, was observed along with matrix remodelling. Caveola recruitment precedes and is required for invadosome formation and activity. Reciprocally, invadosome disruption results in the accumulation of fibril-associated caveolae. Moreover, caveolae and the collagen receptor β1 integrin co-localize at contact sites with the fibrils, and integrins control caveola recruitment to fibrils. In turn, caveolae mediate the clearance of β1 integrin and collagen uptake in an invadosome-dependent and collagen-cleavage-dependent mechanism. Our data reveal a reciprocal interplay between caveolae and invadosomes that coordinates adhesion to and proteolytic remodelling of confining fibrils to support tumour cell dissemination.
CRIS-Team Scopus Importer:2024-02-19